Mineral Chemistry of Index Minerals and Their Implications in the Genesis of the Baba Ali Magnetite Skarn Deposit, Western Iran - ZAMANIAN, HASSAN; PAZOKI, AMIR; AREF ALAVI, SAYED (Asian Journal of Chemistry, 2010)
The Almoughlagh Batholith, consisting chiefly of quartz syenite and syenogranite rocks, belongs to the magnetite series granitoids, is mostly of I-type, metaluminous and calk-alkaline in nature. The batholoth invaded both the Baba Ali diorite and Songor Series culminated in thermal and hydrothermal metamorphic aureoles in which Baba Ali magnetite deposit formed. Petrography and geochemistry of the host rocks and index minerals such as garnet, pyroxene and magnetite reveal a descending temperature regime, beginning at the peak of thermal metamorphism (550 ºC) and ending with the main phase of magnetite mineralization (350-400 ºC). Mineral chemistry of prograde minerals namely garnet and pyroxene implemented to classify the Baba Ali as a typical Fe-Skarn deposit.